2007
DOI: 10.1007/s10535-007-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth dynamics of Calamagrostis epigejos after defoliation as affected by nitrogen availability

Abstract: Young plants of a rhizomatous grass Calamagrostis epigejos (L.) Roth were grown from seed in nutrient solutions containing nitrogen in concentrations 0.1, 1.0, and 10 mM. After six weeks of cultivation the plants were defoliated and changes in growth parameters and in content of storage compounds were measured in the course of regrowth under highly reduced nitrogen availability. Plants grown at higher nitrogen supply before defoliation had higher amount of all types of nitrogen storage compounds (nitrates, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…It uses the guerrilla strategy of clonal growth (Rebele & Lehmann ) to spread rapidly in previously unoccupied communities diversity of which is consequently reduced by competitive exclusion of subordinate species (Somodi, Virágh & Podani ; Rebele ). The competitive success of the C. epigejos lies in its ability to store and translocate resources below ground (Rebele & Lehmann ; Kavanová & Gloser ; Gloser, Košvancová & Gloser ) and high nutrient use efficiency (Yuan et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…It uses the guerrilla strategy of clonal growth (Rebele & Lehmann ) to spread rapidly in previously unoccupied communities diversity of which is consequently reduced by competitive exclusion of subordinate species (Somodi, Virágh & Podani ; Rebele ). The competitive success of the C. epigejos lies in its ability to store and translocate resources below ground (Rebele & Lehmann ; Kavanová & Gloser ; Gloser, Košvancová & Gloser ) and high nutrient use efficiency (Yuan et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many publications about the physiology and ecology of Calamagrostis epigejos [13,19,27,28]. However, its expansion mechanism and the dynamics of changes it causes in grassland communities and habitats still remain relatively poorly explained.…”
Section: Introductionmentioning
confidence: 99%
“…The mobilization of reserve compounds may be limited more by N than C stores, since N uptake can be severely reduced or even interrupted for several days after defoliation (Clement et al 1978;Jarvis & MacDuff 1989). According to Gloser et al (2007), N reserves can support re-growth of plants after defoliation even under fluctuating external N availabilities. In contrast, Turner et al (2006b) pointed out that N reserves were found to play a minor role during re-growth of cocksfoot (Dactylis glomerata L.), indicating that the reliance on N as a plant reserve has not been conclusively established.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are used as substrates in respiration, N reserves are still not as important as carbohydrate reserves in supporting re-growth (White 1973). However, Ourry et al (1988Ourry et al ( , 1989 and Gloser et al (2007) concluded that N compounds are important components interfering with restoration of sward leaf area index (LAI) and growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation